Technology Integration in Learning Design to Improve PGMI Students' Mathematical Communication Skills on the Concept of Integers - Suharti, Suharti; Mulbar, Usman; Talib, Ahmad (UNNES JOURNAL, 2024)
The development of technology encourages the world of education to be able to integrate it into learning design. By integrating technology into learning, students not only get more sophisticated tools to understand and manage mathematical concepts, but also strengthen their skills in communicating mathematical ideas clearly and effectively so that able to support the development of students' mathematical communication skills. Therefore, prospective elementary school teachers must prepare themselves to face the challenges of education in a better digital era. This study aims to analyze the effectiveness of technology integration such as YouTube, Kahoot, and PhET in learning design to improve mathematical communication skills of elementary school teacher education program (PGMI) students on the concept of integers. The type of research used is a quantitative approach with a quasi-experimental method with a posttest-only control design. The posttest-only control design was chosen for this study because the focus is on a direct comparison of the results between the experimental group and the control group after the treatment was given. The sample in this study involved 74 PGMI students who were divided into 38 students in the experimental group and 36 students in the control group. The experimental group received learning with technology integration, while the control group used conventional methods. Data were collected through a mathematical communication skills test. Data analysis used descriptive and inferential statistics, namely the independent sample t-test. The results showed that there were differences in the mathematical communication skills of the experimental group compared to the control group. The experimental group showed better abilities in terms of compiling mathematical arguments, using mathematical symbols and terms clearly, and effectiveness in explaining the concept of integers. Technology integration in learning has proven effective in improving students' mathematical communication skills on the topic of integers. These findings provide practical implications that the integration of technology in learning needs to be optimized to support mathematics learning in the digital era. Prospective teachers need to be prepared with the skills to use technology in learning design. Perkembangan teknologi mendorong dunia pendidikan untuk dapat mengintegrasikannya dalam desain pembelajaran. Dengan mengintegrasikan teknologi ke dalam pembelajaran, mahasiswa tidak hanya mendapatkan alat yang lebih canggih untuk memahami dan mengelola konsep matematika, tetapi juga memperkuat keterampilan mereka dalam mengomunisasikan ide-ide matematika secara jelas dan efektif sehingga mampu mendukung pengembangan kemampuan komunikasi matematis mahasiswa. Untuk itu, calon guru sekolah dasar harus mempersiapkan diri dalam menghadapi tantangan pendidikan di era digital yang lebih baik. Penelitian ini bertujuan untuk menganalisis efektivitas integrasi teknologi such as YouTube, Kahoot, and PhET dalam desain pembelajaran untuk meningkatkan kemampuan komunikasi matematis mahasiswa Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) pada konsep bilangan bulat. Adapun jenis penelitian yang digunakan ialah pendekatan kuantitaif dengan metode quasi eksperimen dengan desain kontrol posttest-only. Desain kontrol posttest-only dipilih untuk penelitian ini karena fokusnya adalah pada perbandingan langsung hasil akhir antara kelompok eksperimen dan kelompok kontrol setelah perlakuan diberikan. Adapun sampel dalam penelitian ini melibatkan 74 mahasiswa PGMI yang dibagi menjadi 38 mahasiswa kelompok eksperimen dan 36 mahasiswa kelompok kontrol. Kelompok eksperimen menerima pembelajaran dengan integrasi teknologi, sementara kelompok kontrol menggunakan metode konvensional. Data dikumpulkan melalui tes kemampuan komunikasi matematis. Analisis data menggunakan statistik deskriptif dan inferensial, yakni uji – t indepentent sampel t-test. Hasil penelitian menunjukkan terdapat perbedaan dalam kemampuan komunikasi matematis kelompok eksperimen dibandingkan kelompok kontrol. kelompok eksperimen menunjukkan kemampuan yang lebih baik dalam hal menyusun argumen matematis, penggunaan simbol dan istilah matematika secara jelas, serta keefektifan dalam menjelaskan konsep bilangan bulat. Integrasi teknologi dalam pembelajaran terbukti efektif dalam meningkatkan kemampuan komunikasi matematis mahasiswa pada topik bilangan bulat. Temuan ini memberikan implikasi praktis bahwa integrasi teknologi dalam pembelajaran perlu dioptimalkan untuk mendukung pembelajaran matematika di era digital. Selain itu, calon guru perlu dipersiapkan dengan keterampilan menggunakan teknologi dalam desain pembelajaran.